Povratak otpisanih (Epizoda 10) - Vodovod - Đorđević, Aleksandar (Yugoslavia : RTV Beograd, 1976)
The DVD includes two new episodes as this excellent TV-series on the Belgrade communist resistance gradually approaches its end. The tenth episode starts of with Prle meeting his old school friend Pufna, who tells him that the Germans plan to destroy the water supply system before they leave. Tihi warns Prle that his friend might be working for the Germans so Prle checks him out while the rest set off to examine the main pumping station. In cooperation with two insiders the attack is set for 9 o’clock the following evening, but just before that the Germans lock all the civilian workers in the basement and the plan has to change, with the group entering the building on their own. They set free the captives and capture the pumping station, but one of the officers manages to escape and, still determined to carry out the demolition, kills Pufna before he is shot down himself. The German authorities realize that sabotage is going on, but there is nothing they can do.
Keywords: Yugoslavia